Omega-3 Phospholipids from Krill Oil Enhance Intestinal Fatty Acid Oxidation More Effectively than Omega-3 Triacylglycerols in High-Fat Diet-Fed Obese Mice - Kroupova, Petra; van Schothorst, Evert M; Keijer, Jaap; Bunschoten, Annelies; Vodicka, Martin; Irodenko, Ilaria; Oseeva, Marina; Zacek, Petr; Kopecky, Jan; Rossmeisl, Martin; Horakova, Olga (Nutrients, 2020)
Antisteatotic effects of omega-3 fatty acids (Omega-3) in obese rodents seem to vary depending on the lipid form of their administration. Whether these effects could reflect changes in intestinal metabolism is unknown. Here, we compare Omega-3-containing phospholipids (krill oil; ω3PL-H) and triacylglycerols (ω3TG) in terms of their effects on morphology, gene expression and fatty acid (FA) oxidation in the small intestine. Male C57BL/6N mice were fed for 8 weeks with a high-fat diet (HFD) alone or supplemented with 30 mg/g diet of ω3TG or ω3PL-H. Omega-3 index, reflecting the bioavailability of Omega-3, reached 12.5% and 7.5% in the ω3PL-H and ω3TG groups, respectively. Compared to HFD mice, ω3PL-H but not ω3TG animals had lower body weight gain (-40%), mesenteric adipose tissue (-43%), and hepatic lipid content (-64%). The highest number and expression level of regulated intestinal genes was observed in ω3PL-H mice. The expression of FA ω-oxidation genes was enhanced in both Omega-3-supplemented groups, but gene expression within the FA β-oxidation pathway and functional palmitate oxidation in the proximal ileum was significantly increased only in ω3PL-H mice. In conclusion, enhanced intestinal FA oxidation could contribute to the strong antisteatotic effects of Omega-3 when administered as phospholipids to dietary obese mice.
Keywords: Male; střeva; Fatty Acids, Omega-3; Omega-3 index; Oxidation-Reduction; Phospholipids; Omega-3 phospholipids; high-fat diet; omega-3 mastné kyseliny; triglyceridy; dieta s vysokým obsahem tuků; Animals; metabolismus lipidů; tělesná hmotnost; Body Weight; Intestines; Oils; myši obézní; střevní sliznice; oleje; Lipid Metabolism; mastné kyseliny; mužské pohlaví; fosfolipidy; Intestinal Mucosa; oxidace-redukce; krevní glukóza; Euphausiacea; Mice, Obese; Fatty Acids; zvířata; Diet, High-Fat; krill oil; Erythrocyte Membrane; Triglycerides; Blood Glucose; erytrocytární membrána; small intestine